التشوهات المعرفية لدى طلاب مرحلة الدراسة الاعدادية - عبد الزهرة مزعل, فاضل; رسـن شـنـدوخ, عــلــي (Journal of College of Education, 2019)
The study aims at investigating the effect of cognitive reconstruction and reframing styles on the cognitive distortion in high school students.     In order to know the cognitive distortion in high school students, the researcher adopts Al-Alawi 2013 scale which is constructed by the author according the behavioral cognitive theory of Beck. In order to construct the counseling program by the two styles, the scale is conducted on a sample of 140 high school students from Thi Qar to reveal the cognitive reframing in high-school students who need this program. After that, 30 students with high cognitive reframing have been selected. The sample is divided into three groups: first experimental, second experimental, and control group. After applying t-test and the mean, the study finds out that the cognitive distortion in high- school students is less than the theoretical mean of the study which means there is no cognitive distortion in the sample of the study.